2013
DOI: 10.1097/sle.0b013e318275745a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Therapy Using Partial Splenic Embolization and Transjugular Retrograde Obliteration on Systemic Hemodynamics in Patients With Gastric Varices and a Splenorenal Shunt

Abstract: : We conclude that the combined therapy using PSE and TJO reduces the splenic venous flow and stops the splenorenal shunt flow, which improves the arterio-venous oxygen content difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Partial splenic embolization can reduce the SVF and WHVP [22]. Our preliminary report [23] showed that the combined therapy using partial splenic embolization and TJO reduced the SVF and stopped SRS flow, which improved the C(a-v) O 2 . However, the effect of TJO or partial splenic embolization on systemic hemodynamics is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Partial splenic embolization can reduce the SVF and WHVP [22]. Our preliminary report [23] showed that the combined therapy using partial splenic embolization and TJO reduced the SVF and stopped SRS flow, which improved the C(a-v) O 2 . However, the effect of TJO or partial splenic embolization on systemic hemodynamics is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…When symptoms associated with splenomegaly (abdominal pain and compression) or a tendency to bleed and severely decreased blood cells (at least one of the following: platelets, ≤5 × 10 4 ; white blood cells, ≤3000; and red blood cells, ≤300 × 10 4 ) associated with splenomegaly, partial splenic embolization or splenectomy should be considered …”
Section: Guidelines For Treatment Of Aberrant Portal Hemodynamicsmentioning
confidence: 99%
“…When symptoms associated with splenomegaly (abdominal pain and compression) or a tendency to bleed and severely decreased blood cells (at least one of the following: platelets, ≤5 × 10 4 ; white blood cells, ≤3000; and red blood cells, ≤300 × 10 4 ) associated with splenomegaly, partial splenic embolization or splenectomy should be considered. 19,106,[136][137][138][139][146][147][148]167,168,[180][181][182][183][184][185][186][187][188][189][190][191][192][193] Guidelines for treatment of stenosis and obstruction in BCS Obstruction or stenosis of the main trunk of the hepatic vein or the hepatic segment of the inferior vena cava should be treated by recanalization or dilatation with a catheter, stent placement, surgery to directly eliminate the obstruction and stenosis, or a shunt operation between the upper and lower sites of obstruction and stenosis of the vena cava. 131,[194][195][196][197][198][199][200][201][202][203][204][205][206] In acute cases with thrombus obstruction up to the peripheral part of the hepatic vein, the liver resection and peripheral hepatic vein-right atrium anastomosis may be an option.…”
Section: Guidelines For Treatment Of Splenomegaly and Hypersplenismmentioning
confidence: 99%